PARTNERSHIPS TO IMPROVE AGING IN CALIFORNIA: PERSPECTIVES FROM HRSA'S GERIATRIC WORKFORCE ENHANCEMENT PROGRAMS. (11th November 2018) - Neumann, A; Stevens, G; Richter Lagha, R; Sorkin, D; Guerrero, L; Patel, D; Madanat, H
Abstract: Background: To improve models of care for older adults, HRSA's Geriatrics Workforce Enhancement Program (GWEP) encouraged academic institutions to partner with health and/or social service providers. In 2016, evaluators from five California GWEPs began to study their partnerships and to determine characteristics of success. Methods: Evaluators developed a mixed-method approach. Partners (n=38) completed a survey that measured five attributes (governance, administration, autonomy, mutuality, and norms/trust) with a 17-item instrument, and perceived success with an 8-item instrument. To determine context, experiences and results, evaluators conducted semi-structured, 15-question interviews that were audio recorded and transcribed for thematic analysis. Through iterative coding by consensus, a code structure emerged and was applied to all interviews. Results: Partners reported high levels of success (mean=8.2, 10-point scale), and scores for attributes ranged from 5.9 (7-point scale) for administration to 6.4 for autonomy with mutuality (odds ratio of 8.1, p=0.002) and norms/trust (odds ratio=19.0, p=0.019) most highly correlated with success. Interviews with 20 organizations captured a range of partnership structures, from coordination to collaboration, and experiences of dissatisfaction were associated with a failure to acknowledge differences in applied goals. Discussion: To meet the goals of HRSA's GWEP initiative to improve care for older adults, successful cross-sector partnerships are critical. A mixed-method study of five diverse GWEPs in California showed that partnership aspects of mutuality (e.g., all partners benefit from the collaboration) and norms/trust (e.g., organizations can count on each other) appeared to contribute the most to perceived success. Additionally, prioritizing understanding of applied goals can decrease dissatisfaction.